Tres teorías del conflicto intelectual: Randall Collins, Pierre Bourdieu y Harold Bloom - Bellón Aguilera, José Luis (Romanica Silesiana)
This article focuses on three conflict theories of intellectual creativity (by Randall Collins (born 1941), Pierre Bourdieu (1930—2002) and Harold Bloom (born 1930)). All three systems, despite their differences, are useful for literary theory and criticism. The purpose of this article is to explore them. Both, simple pseudo-sociological reductions and excessive academic textualizations are ineffectual for analyses of literary artifacts and intellectual creativity. Key words: Sociology, Collins, Bourdieu, Bloom, anxiety of influence.